COMPARISON OF END TO END ANASTOMOTIC URETHROPLASTY AND OPTICAL URETHROTOMY IN THE MANAGEMENT OF PATIENTS PRESENTING WITH SHORT SEGMENT INCOMPLETE URETHRAL STRICTURE - Amer Abbas; Sajid Mumtaz Qazi; Anam Altaf (Journal of University Medical & Dental College, 2018)
ABSTRACT: OBJECTIVE: To compare end to end urethroplasty and optical urethrotomy in terms of postoperative urinary ﬂow rate in patients presenting with short segment incomplete urethral stricture. STUDY DESIGN: Randomized controlled trial (RCT). PLACE AND DURATION WITH DATES: The study was conducted in department of Urology, Pakistan Institute of Medical Sciences (PIMS), Islamabad. The duration of study was 1 year. METHODOLOGY: In present study, 47 patients were randomly allocated to each of the intervention groups i.e. Group A underwent end to end urethroplasty procedure and Group B underwent optical urethrotomy. Peak urinary ﬂow rates were measured preoperatively, at one week after the catheter removal post operatively and at 3 months after the catheter removal post operatively. Outcome in both groups was compared using ’t’ test. RESULTS: Mean age of patients in group A (End to End anastomotic Urethroplasty) was 31.98±11.14SD while mean age in Group B (Optical Urethrotomy) was 34.72±13.76SD. The mean peak urinary ﬂow rate was found to be 21.39 ml/sec ± 1.89 SD in Group A and was 22.11 ml/sec ± 2.05 SD in Group B at one week post operatively after catheter removal (P> 0.05). The mean peak urinary ﬂow rate was found to be 22.48 ml/sec ± 2.12 SD in Group A and was 17.99 ml/sec ± 1.52 SD in Group B at 3 months post operatively after catheter removal (P<0.05). CONCLUSION: End to end anatsomotic urethroplasty was found to be signiﬁcantly better than optical urethrotomy in terms of peak urinary ﬂow rate at one week and 3 months after catheter removal in the treatment of urethral strictures in men.